2022
DOI: 10.1155/2022/8169849
|View full text |Cite
|
Sign up to set email alerts
|

Ecolabel with Augmented Reality on the Website to Enhance Student Environmental Awareness

Abstract: Industrial Revolution 4.0, accompanied by an environmental crisis, shows that modernization and technological sophistication do not make harmonization between nature and humans more closely intertwined. This harmony needs ecological consciousness nurtured from an early age which is a challenge for the Industrial Revolution 4.0. Using technology in this research aimed to examine enhancing student environmental awareness affected by ecolabel with web-based augmented reality at elementary schools in Setia Budi su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The need to include more interactive educational material as well as clear explanations and guidelines when displaying information through augmented reality was highlighted. Aiming at enhancing student environmental awareness, Safitri et al (2022) carried out a study examining the use of augmented reality in the context of environmental education. Their study followed an experimental design and a total of 286 students (experimental group: 143 students and control group: 143 students) took part.…”
Section: Augmented Reality In Earth and Environmental Sciences Educationmentioning
confidence: 99%
“…The need to include more interactive educational material as well as clear explanations and guidelines when displaying information through augmented reality was highlighted. Aiming at enhancing student environmental awareness, Safitri et al (2022) carried out a study examining the use of augmented reality in the context of environmental education. Their study followed an experimental design and a total of 286 students (experimental group: 143 students and control group: 143 students) took part.…”
Section: Augmented Reality In Earth and Environmental Sciences Educationmentioning
confidence: 99%
“…Regarding views on-and perception of environmental activism, stewardship, action and governance, many studies have engaged with the theme of students as activist [137], and environmental education focuses on how to teach students to gain knowledge [131] and to instill [138][139][140][141] and predict [142][143][144] environmentally responsible behavior, including on campus [145][146][147]. Studies have reported on educating students on action-related strategies [138,[148][149][150][151][152], instilling action in students [139,140,, and predicting action [175,182,183]. It has been argued that teachers do not feel equipped to teach environmental action strategies [149], and teaching methods have been questioned [184].…”
Section: Environmental Activism and Studentsmentioning
confidence: 99%
“…It has been argued that "university students are regarded as future decision-makers in society and have a high likelihood of becoming opinion-shapers in terms of the environment" [204] (p. 958). Studies have reported on students being educated in environmentrelated action strategies [138,[148][149][150][151][152], instilling action in students [139,140, and predicting action [175,182,183]. It has been argued that "determining the factors that influence young adults' engagement in environmental action is critical to further developing their active and important participation in environmental issues" [202] (p. 612).…”
Section: Students and Environmental Activismmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for media usage in the learning process can be an effective solution by conducting learning conditions to become more accurate. Teachers can use various learning media: simply through conventional or multimedia-based teaching tools, known as interactive learning media (Kucirkova & Flewitt, 2020;Marini et al, 2022;Nuraini et al, 2020;Rihatno et al, 2020;Safitri et al, 2022b;Sujarwo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%